Role of Silk Fibroin in Modulating Thermo-responsive Behavior of PNIPAM Hydrogels - Baniasad , Arezou (Biocompounds, 2026)
Thermo-responsive hydrogels based on Poly N-Isopropylacrylamide (PNIPAM) have attracted significant attention for advanced biomedical applications due to their smart response near physiological temperature. In this study, Silk Fibroin (SF) was incorporated into PNIPAM hydrogels to develop a tunable composite system with enhanced physicochemical properties. The hydrogels were successfully synthesized via free radical polymerization, and the effect of SF content (0–15 wt%) on the thermo-responsive behavior, swelling characteristics, deswelling kinetics, and network stability was systematically investigated. The results demonstrated that the incorporation of SF led to a gradual increase in the Lower Critical Solution Temperature (LCST), shifting from 32.1 °C for pure PNIPAM to 34.6 °C for the highest SF content. Swelling studies revealed a reduction in equilibrium Swelling Ratio (SR) with increasing SF concentration at 25 °C, while maintaining controlled water retention above LCST. Deswelling analysis showed a more gradual water release behavior in SF-containing hydrogels compared to pure PNIPAM, indicating improved regulation of thermo-responsive collapse. Additionally, gel fraction results confirmed enhanced network stability and crosslinking efficiency with increasing SF content, reaching up to 90.3%. Overall, the incorporation of SF effectively modulated the structural and thermo-responsive properties of PNIPAM hydrogels, resulting in a more stable and controllable hydrogel system. These findings highlight the potential of PNIPAM/SF composite hydrogels for biomedical applications such as controlled drug delivery, tissue engineering, and smart biomaterials.